PENGARUH KONSOLIDASI TERHADAP DEFORMASI DAN FAKTOR KEAMANAN DENGAN MODEL MATERIAL TANAH LUNAK - O.B.A Sompie; T. Ilyas; B.I. Setiawan; Indartod Indartod (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2017)
Material models are always required to know the characteristics (physical and mechanical properties) of the soil layer at the site by using analysis of geotechnical studies that have been done in the field and in laboratories. Soils such as clay, silty clay and peat show a high degree of compressibility compared to other soils. In oedometer testing, the consolidated clay normally behaves up to ten times softer than the normally consolidated sand. This study aims to determine the soft consolidation behavior of soft clay primers by comparing the results obtained from finite element analysis calculations on Plaxis 2D with analytical calculations and survey measurements. Two different material models were used during finite element calculations, comparing the performance of Soft Soil Model, SSM models to the Mohr-Coulomb Model (MCM) model commonly used today. Practical geotechnical analysis of stability of embankment construction is done by using Plaxis 8 computer program, based on Finite Element Method to analyze deformation value and safety factor with construction phase of consolidation. Keywords: Consolidation, deformation, safety facor, SSM